2022
DOI: 10.3389/fcvm.2021.831734
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Heart Failure: Landscape, Challenges, and Future Directions

Abstract: Heart failure (HF) is a major global healthcare problem accounting for substantial deterioration of prognosis. As a complex clinical syndrome, HF often coexists with multi-comorbidities of which cognitive impairment (CI) is particularly important. CI is increasing in prevalence among patients with HF and is present in around 40%, even up to 60%, of elderly patients with HF. As a potent and independent prognostic factor, CI significantly increases the hospitalization and mortality and decreases quality of life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 182 publications
0
22
0
2
Order By: Relevance
“…Chronic HF is a complex clinical syndrome that often coexists with multiple comorbidities. MCI appears to be a particularly important condition in HF [ 7 ], although reports on its prevalence vary between 25% and 75% across population-based studies due to variation in definitions and diagnostic criteria [ 23 , 24 , 25 , 26 , 27 ]. Patients with HF typically exhibit MCI in the domains of memory, working memory, attention, processing speed, and executive function [ 25 , 28 ].…”
Section: Cognitive Decline and Dementia In Common Cardiac Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic HF is a complex clinical syndrome that often coexists with multiple comorbidities. MCI appears to be a particularly important condition in HF [ 7 ], although reports on its prevalence vary between 25% and 75% across population-based studies due to variation in definitions and diagnostic criteria [ 23 , 24 , 25 , 26 , 27 ]. Patients with HF typically exhibit MCI in the domains of memory, working memory, attention, processing speed, and executive function [ 25 , 28 ].…”
Section: Cognitive Decline and Dementia In Common Cardiac Disordersmentioning
confidence: 99%
“…Patients with HF typically exhibit MCI in the domains of memory, working memory, attention, processing speed, and executive function [ 25 , 28 ]. In patients with HF, MCI was shown to significantly increase the risk of hospitalization and mortality, and decrease quality of life [ 7 ]. Chronic HF is also associated with an increased risk of dementia and AD in older adults [ 29 ].…”
Section: Cognitive Decline and Dementia In Common Cardiac Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, Hammond et al [ 10 ] found that cognitive decline was similar in HF patients with reduced versus preserved ejection fraction. In HF patients with preserved ejection fraction, the mechanisms for cognitive decline are likely related to obesity, vascular impairment, diastolic dysfunction, chronic neurohormonal activation [ 48 ].…”
Section: Cardiovascular Disease and Brain Healthmentioning
confidence: 99%
“… 3 , 4 , 5 Cognitive impairment imposes a detrimental health burden on HF patients, as it negatively impacts quality of life, self-care management, treatment adherence, hospitalisation rates, and mortality. 6 Interventions that prevent, slow down, or reverse cognitive decline in HF patients are desperately needed; however, a lack of mechanistic insight has limited the number of safe and effective pharmaceutical interventions.…”
Section: Introductionmentioning
confidence: 99%